Mencapai Sustainability Koperasi Pesantren melalui Jiwa Entrepreneurship pada Mahasantri Lembaga Tinggi Pesantren Luhur Malang - Nihayatu aslamatis Solekah; Titis Miranti; Barianto Nurasri Sudarmawan (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2020)
Entrepreneurship is proven to be able to move the economics. Specifically, entrepreneurial activities within the pesantren are increasingly prevalent. This condition makes the ministry of industry also participate in developing cooperatives through Islamic boarding schools throughout the nation for now. The Lembaga Tinggi Pesantren Luhur Malang is one of the boarding schools in Malang, precisely at the Ketawanggede, Lowokwaru District. In addition to religious education in the form of recitation, halaqoh, prayer in congregation, this boarding school also focuses on giving students understanding and education in the economic field. The purpose of this service is to provide assistance in the form of cooperative management through the spirit of entrepreneurship of the students of Malang Luhur Pesantren. The method used in this service is Participatory Action Research (PAR). This dedication found that at Luhur Malang, there are a lot of ideas about entrepreneurship, even among those who have carried out these activities. However, its management still needs to be improved again. Therefore, this dedication recommends the need to continuously increase the resources of students who are able to market the results of pesantren cooperatives that can increase economic use value and the need for support and supervision among each LTPLM member